Analysis of Students’ Abilities in Solving Numeracy Literacy Problems in Mathematics Learning at the Junior High School/ MTS Muhammadiyah in Sorong Regency - Astripin Jeane Surupanggil; Surya Putra Raharja; Suhartini Sumadi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Numeracy literacy is the ability to understand, reason, and apply basic mathematical concepts in everyday life. The relationship between numeracy and mathematics is that numeracy requires mathematical knowledge learned in the curriculum; however, mathematics learning does not necessarily develop students' numeracy skills. An indicator of educational achievement across countries that Indonesia participates in is the Programme for International Student Assessment (PISA) score, where Indonesia ranks 63rd out of 81 countries in mathematics. This study aims to describe students' abilities in solving numeracy literacy problems in mathematics learning at the junior high school (MTS) Muhammadiyah in Sorong Regency. The research was conducted at SMP UNIMUDA Pulau Arar, SMP Muhammadiyah 2 Mariyai, and SMP Muhammadiyah Aimas. The type of research is qualitative descriptive. The results show that out of 44 students who completed the questions, five students fell into the high category, 31 students into the medium category, and eight students into the low category. Student responses varied for each answer in meeting the indicators of numeracy literacy ability